PEMANFAATAN ARDUINO UNO DALAM TONG SAMPAH PINTAR DAN PENDETEKSI ASAP BERBASIS IR SENSOR - Vitri Roma Sari; Suhada Suhada; Anjar Wanto; Dedy Hartama; Irawan Irawan (Device, 2022)
Garbage is unwanted material after the end of a process. Good waste management can create a clean environment and avoid various diseases. understanding of waste management to this day is still widely ignored by the community, many people forget the function of trash cans and prefer to litter. Not only in the community and in the school environment, in the lecture environment there are still many people who are lazy to dispose of garbage in their place because they are lazy to open the lid of the garbage can because it is smelly and dirty. If a small piece of garbage is dumped into a place that is not where it is and is carried out every day by the community then that garbage will eventually accumulate everywhere and will invite disease and even flooding. Therefore, the authors designed an automatic open-lid trash can based on Arduino and IR Sensor in order to make it easier for everyone to dispose of waste. This smart trash can is also equipped with sensors that will detect fires around the trash can. By utilizing Arduino Uno, MG90S Micro Servo, Infrared Sensor, Mq2 sensor and buzzer. Micro Servo MG90S will be used in opening and closing trash cans, Mq2 sensors are used to detect gas leaks or smoke, and Buzzer will be used as a notification if the mq2 sensors detect the presence of smoke and gas leaks in the room. Then enter into making computer programs and describe the code and diagrams. The results obtained from the system test are that the trash can, can open and close automatically and can detect any fire symptoms around it.